Quantum time delay in the gravitational field of a rotating mass. (26th July 2017) - Battista, Emmanuele; Tartaglia, Angelo; Esposito, Giampiero; Lucchesi, David; Ruggiero, Matteo Luca; Valko, Pavol; Dell'Agnello, Simone; Di Fiore, Luciano; Simo, Jules; Grado, Aniello
Abstract: We examine quantum corrections of time delay arising in the gravitational field of a spinning oblate source. Low-energy quantum effects occurring in Kerr geometry are derived within a framework where general relativity is fully seen as an effective field theory. By employing such a pattern, gravitational radiative modifications of Kerr metric are derived from the energy–momentum tensor of the source, which at lowest order in the fields is modelled as a point mass. Therefore, in order to describe a quantum corrected version of time delay in the case in which the source body has a finite extension, we introduce a hybrid scheme where quantum fluctuations affect only the monopole term occurring in the multipole expansion of the Newtonian potential. The predicted quantum deviation from the corresponding classical value turns out to be too small to be detected in the next future, showing that new models should be examined in order to test low-energy quantum gravity within the solar system.